2021
DOI: 10.1111/ajco.13593
|View full text |Cite
|
Sign up to set email alerts
|

Physalin B inhibits cell proliferation and induces apoptosis in undifferentiated human gastric cancer HGC‐27 cells

Abstract: Background Physalin B (PB) from Physalis angulata L. (Solanaceae) is a naturally occurring secosteroid with multiple biological activities, including anti‐inflammatory and anticancer activity. However, PB's effects and mechanisms in human gastric cancer (GC) cells are not well characterized. Methods The undifferentiated GC cell line HGC‐27 and semi‐differentiated GC cell line SGC‐7901 were treated with PB. Cell counting kit‐8 (CCK‐8) and colony formation assays were performed to evaluate cell viability. Apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…By altering mitochondrial function, physalin B causes G2/M cell cycle arrest and cell death in human non-small cell lung cancer cells (A549) and a cell line for human breast cancer (MCF-7) affects p53-dependent signaling. The survival and proliferation of the undifferentiated gastric cancer cell line, HGC-27, and the ability to produce clones were all inhibited by physalin B, which induces G0/G1 cell cycle arrest and caspase 8, 3, 7 and poly (ADP-ribose) polymerase cleavage ( 17 ). In 2006, Magalhães et al ( 18 ) conducted in vivo studies investigating the antitumor activity of P. angulata L. using mice bearing sarcoma 180 tumor cells, confirming the antitumor activity of physalin B and D.…”
Section: Anticancer Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…By altering mitochondrial function, physalin B causes G2/M cell cycle arrest and cell death in human non-small cell lung cancer cells (A549) and a cell line for human breast cancer (MCF-7) affects p53-dependent signaling. The survival and proliferation of the undifferentiated gastric cancer cell line, HGC-27, and the ability to produce clones were all inhibited by physalin B, which induces G0/G1 cell cycle arrest and caspase 8, 3, 7 and poly (ADP-ribose) polymerase cleavage ( 17 ). In 2006, Magalhães et al ( 18 ) conducted in vivo studies investigating the antitumor activity of P. angulata L. using mice bearing sarcoma 180 tumor cells, confirming the antitumor activity of physalin B and D.…”
Section: Anticancer Propertiesmentioning
confidence: 99%
“…P. angulata L. contains active ingredients that have medicinal properties. These active substances are: i) Physalin A in the roots, with antiparasitic properties ( 23 ), ii) physalin B in the whole plant, with anti-inflammatory, antiparasitic, antibacterial, anticancer and antifibrotic properties ( 10 , 16 , 17 , 27 , 29 , 31 , 37 , 43 ), iii) physalin D, F, G in the whole plant, with anti-inflammatory, antiparasitic and antibacterial properties ( 11 , 20 , 23 , 32 , 34 , 43 ), iv) physalin E in the whole plant, with anti-inflammatory and antiparasitic properties ( 23 ), v) physalin H in the root, with antiparasitic properties ( 20 , 31 ), vi) withangulatin A in the fruit, with antidiabetic properties ( 35 ) and vii) physangulatin A in the leaves and stems, with anti-inflammatory properties ( 35 ). The active substances in P. angulata L. are also presented in Table II and Fig.…”
Section: Chemical Components Of Physalis Angulata ...mentioning
confidence: 99%
“…In general, the cytotoxic activity of physalins was shown to be related to induction of programmed cell death ( Vandenberghe et al, 2008 ; Hsu et al, 2012 ; Wu et al, 2012 ; He et al, 2013a ; Ma et al, 2015 ; Fang et al, 2021 ; Yang et al, 2021 ). Physalins A, B, and F may trigger apoptosis through activation of the intrinsic pathway of poly (ADP-ribose) polymerase (PARP) cleavage ( Wu et al, 2012 ; He et al, 2013a ; Ma et al, 2015 ).…”
Section: Anticancer Activitymentioning
confidence: 99%
“…In this sense, Yang et al (2021) also concluded that physalin F was able to induce apoptosis in HT1080 cells mainly through the inhibition of the enzyme isocitrate dehydrogenase (IDH). Conversely, Fang et al (2021) demonstrated that, when physalin B treatment was performed in HGC-27 cells, the cell cycle-related proteins cyclin D1, cyclin D3, CDK4, CDK6, cyclin E, and the phosphorylated retinoblastoma tumor suppressor protein (p-Rb) were downregulated in a concentration-dependent manner, without activation of the intrinsic apoptosis pathway. Another important finding is that physalins stimulate the production of reactive oxygen species (ROS) and NO, which are important mediators responsible for triggering cell death by apoptosis ( Wu et al, 2012 ; He et al, 2013b ; He et al, 2014 ).…”
Section: Anticancer Activitymentioning
confidence: 99%
“…And its mortality rate ranks third among malignant tumors ( Ajani et al, 2022 ). Its 5-year survival rate is around 20%, posing a serious threat to human health ( Fang et al, 2021 ; Guo et al, 2021 ). In 2018, the number of newly diagnosed cases of stomach cancer is well over one million, and the number of deaths is increasing every year ( Zhao et al, 2016 ; Zhang and Yu, 2020 ).…”
Section: Introductionmentioning
confidence: 99%